2007
DOI: 10.1097/01.shk.0000245026.01365.55
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Function Is Better Preserved in Pigs When Acute Normovolemic Hemodilution Is Achieved With Hydroxyethyl Starch Versus Lactated Ringer's Solution

Abstract: Acute normovolemic hemodilution (ANH) has been proposed to decrease the need for allogenic blood transfusion. Consequently, great amounts of fluids are necessary to maintain hemodynamics during and after blood removal. The aim of this experiment was to evaluate the oxygenation, respiratory compliance, and lung structure during ANH performed with lactated Ringer's solution and hydroxyethyl starch (HES). Gas exchange, extravascular lung water, intrathoracic blood volume, serum osmolality, respiratory mechanics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 39 publications
1
15
0
4
Order By: Relevance
“…4 A recent meta-analysis 5 and different clinical trials 6,7 comparing the use of crystalloids versus colloids in critically ill patients found no differences in outcome. However, several beneficial effects of colloids compared to crystalloids have been shown in the lungs, namely reduced alveolar-capillary permeability, 8 less histological damage, 9 and decreased inflammatory cell infiltration. 10,11 Furthermore, colloids may allow faster hemodynamic stabilization compared to crystalloids.…”
mentioning
confidence: 99%
“…4 A recent meta-analysis 5 and different clinical trials 6,7 comparing the use of crystalloids versus colloids in critically ill patients found no differences in outcome. However, several beneficial effects of colloids compared to crystalloids have been shown in the lungs, namely reduced alveolar-capillary permeability, 8 less histological damage, 9 and decreased inflammatory cell infiltration. 10,11 Furthermore, colloids may allow faster hemodynamic stabilization compared to crystalloids.…”
mentioning
confidence: 99%
“…After fluid loading, the EVLW/PBV ratio was also related to PLI (r ϭ .43). As stated before, HES was not able to reduce vascular permeability, capillary leakage, and pulmonary edema in humans (34,(37)(38)(39) and animals (20,(23)(24)(25)(26)(27)40). Using the same 67 Gallium-transferrin PLI, Verheij et al (39) also clearly confirmed the ability of HES (200/0.5) for ameliorating the increased pulmonary permeability and pulmonary vascular injury caused by cardiac and major vascular surgery as compared with gelatin.…”
Section: Discussionmentioning
confidence: 65%
“…In human (34,(37)(38)(39) and animal (20,(23)(24)(25)(26)(27)40) studies a comparison of HES with crystalloids showed that HES maintained intravascular volume and COP in septic shock (35,36), and reduced vascular permeability, capillary leakage, and pulmonary edema. For the gelatin, the intravascular half-life is relatively short (about 2 hours) and volume expansion effect is low (plasma volume increased equal to the amount infused, with only half remaining after 4 hours) (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some beneficial effects on pulmonary parameters have been demonstrated, including pulmonary permeability [102,103], histological findings [104], reductions in VILI and pulmonary edema [105], and more rapid hemodynamic stabilization [103]. However, in a large systematic review of burns, trauma, and surgical patients, no outcome benefit of colloids could be demonstrated, and hydroxyethyl starch (HES) was found to possibly increase mortality [106].…”
Section: Fluid Choicementioning
confidence: 99%